The Values of Struggle in the Tragedy of "Rengat Berdarah" as Strengthening History Learning in Indragiri Hulu - Pernantah, Piki Setri; Hasibuan, Rizki Ananda; Aprilia, Miranda; Putri, Meliyani; Renaldi, Renaldi; Wulandari, Wingga (Indonesian Journal of History Education, 2023)
Strengthening character education is something that is still very much needed in the midst of a crisis of morals and cultural values in the era of society 5.0. The essence of character education in the context of Indonesian education is education based on the noble values of the Indonesian nation, including historical events that are locality. In this regard, history learning has a considerable contribution in the formation of the nation's character, because historical material is full of meaning and / or character values that can be exemplified, preserved, and used as a guide for life. This paper aims to examine how the reconstruction of the values of the struggle for the Bloody Rengat tragedy can be used as learning material for local history in Indragiri Hulu Regency to internalize values to strengthen character education. The research method used in writing is qualitative with descriptive analysis. Data collection techniques through literature studies. The findings of the values of struggle contained in the tragedy of the Bloody Rengat show the high spirit of patriotism of the Rengat people by willingly sacrificing the body soul regardless of age and gender, the value of a sense of harmony and teaching students to maintain self-esteem for the benefit of the nation. These values can be internalized in learners through locally charged history learning.